Deep neural survival networks for cardiovascular risk prediction: The Multi-Ethnic Study of Atherosclerosis (MESA). (December 2021) - Hathaway, Quincy A.; Yanamala, Naveena; Budoff, Matthew J.; Sengupta, Partho P.; Zeb, Irfan
Abstract: Background: There is growing interest in utilizing machine learning techniques for routine atherosclerotic cardiovascular disease (ASCVD) risk prediction. We investigated whether novel deep learning survival models can augment ASCVD risk prediction over existing statistical and machine learning approaches. Methods: 6814 participants from the Multi-Ethnic Study of Atherosclerosis (MESA) were followed over 16 years to assess incidence of all-cause mortality (mortality) or a composite of major adverse events (MAE). Features were evaluated within the categories of traditional risk factors, inflammatory biomarkers, and imaging markers. Data was split into an internal training/testing (four centers) and external validation (two centers). Both machine learning (COXPH, RSF, and lSVM) and deep learning (nMTLR and DeepSurv) models were evaluated. Results: In comparison to the COXPH model, DeepSurv significantly improved ASCVD risk prediction for MAE (AUC: 0.82 vs. 0.80, P  ≤ 0.001) and mortality (AUC: 0.87 vs. 0.84, P  ≤ 0.001) with traditional risk factors alone. Implementing non-categorical NRI, we noted a >40% increase in correct reclassification compared to the COXPH model for both MAE and mortality ( P  ≤ 0.05). Assessing the relative risk of participants, DeepSurv was the only learning algorithm to develop a significantly improved risk score criteria, which outcompeted COXPH for both MAE (4.22 vs. 3.61, P  = 0.043) and mortality (6.81 vs. 5.52, P  = 0.044). The addition of inflammatory or imaging biomarkers to traditional risk factors showed minimal/no significant improvement in model prediction. Conclusion: DeepSurv can leverage simple office-based clinical features alone to accurately predict ASCVD risk and cardiovascular outcomes, without the need for additional features, such as inflammatory and imaging biomarkers. Graphical abstract: Image 1 Highlights: An innovative implementation of machine/deep learning for cardiac risk prediction. A deep neural survival network (DeepSurv) can outcompete traditional models. With traditional risk factors alone, DeepSurv provides superior outcome prediction. DeepSurv utilizes undervalued features to increase its prediction efficiency. DeepSurv generates risk scores that can augment clinical practice and patient care.